Reformulation of Nominee Agreement Policy in Agrarian Law as an Effort to Harmonize Freedom of Contract with Restrictions on Foreign Land Ownership - Gunawan (Faculty of Law, Universitas Pekalongan, 2025)
The practice of nominee agreements in land ownership by foreign nationals in Indonesia has given rise to a conflict between the principle of freedom of contract in the Civil Code and the principle of agrarian sovereignty in the Basic Agrarian Law. This inconsistency has created legal uncertainty, legal loopholes, and unequal protection for the parties to the agreement. The impact is evident in the prevalence of land disputes and the weak protection of local communities as nominees. This study aims to analyze the normative contradiction between freedom of contract and the prohibition of land ownership by foreigners, and to formulate a model of legal harmonization that ensures legal certainty and agrarian sovereignty. The method used is normative legal analysis, employing an approach that examines regulations, legal principles, and court rulings. This study finds that the practice of nominee agreements in foreign land ownership in Indonesia creates a conflict between the principle of freedom of contract and the principle of agrarian sovereignty. This leads to legal uncertainty, legal evasion, and the risk of exploitation of strategic resources. To address this, legal harmonization is needed by affirming the supremacy of the UUPA and strengthening regulations prohibiting nominee agreements, accompanied by verified green investment schemes.